Wheat (Triticum aestivum L.) grain proteome response to elevated [CO2] varies between genotypes. (May 2017) - S. Arachchige, Pramesha Madurangi; Ang, Ching-Seng; Nicolas, Marc E.; Panozzo, Joe; Fitzgerald, Glenn; Hirotsu, Naoki; Seneweera, Saman
Abstract: The impact of rising carbon dioxide concentration ([CO2 ]) in the atmosphere on wheat grain protein concentration and proteome was investigated in this study. Wheat genotypes (H45, SB003, SB062 and Yitpi) were grown in the Australian Grains Free-Air CO2 Enrichment (AGFACE) facility, Horsham, Victoria, Australia under ambient [CO2 ] (a[CO2 ], 391 μmol mol −1 ) and elevated [CO2 ] (e[CO2 ], 550 ± 20 μmol mol −1 ). Grain yield and grain protein concentration were measured. Global grain proteome comparison was carried out using stable isotope dimethyl labelling followed by liquid chromatography - mass spectrometry (LC-MS/MS). Grain yield was significantly increased at e[CO2 ], whereas protein concentration was significantly decreased and responses varied between genotypes. Proteome-wide analysis revealed that protein composition was also altered under e[CO2 ]. Grain protein concentration and composition of SB003 was very responsive to e[CO2 ]. Mainly storage proteins were decreased at e[CO2 ] and the responses varied between genotypes. These findings suggest that e[CO2 ] may have a major impact on grain protein quality and thus bread quality and human and animal nutrition. Further, these findings suggest that [CO2 ] insensitive cultivars can be identified for grain quality improvement under changing climate. Highlights: Wheat grain protein and proteome response to e[CO2 ] are genotype dependent. Grain proteome changes are associated with protein concentration changes at e[CO2 ]. Storage proteins were mainly affected by e[CO2 ]. Genotypic variation can facilitate grain quality improvement under future climate.